Rediscovery of Malaxis nana (Orchidaceae: Malaxideae) in Costa Rica, with an updated description - Pérez -Escobar, Oscar A. (2014)
Malaxis nana C. Schweinf. is known from two herbarium specimens collected in 1925 in San Ramón, Alajuela province, and three additional specimens without detailed locality data collected in the late 1800’s, all of them in Costa Rica. This species had not been registered since. Malaxis nana is hereby first reported for Las Cruces Biological Station, Puntarenas province, in southern Costa Rica. An updated description, illustration, photographs and distribution map for this taxon are provided.